PEMANFAATAN LIMBAH DAGING BUAH PALA OLEH KELOMPOK WANITA TANI DESA KAIYASA KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN - Adesna Fatrawana; Siti Nurjannah; Abu Rahmat Ibrahim; Adriani (Altifani Journal: International Journal of Community Engagement, 2025)
The widespread use of nutmeg in North Maluku still focuses on the seeds and mace, which are dried and then sold. This often results in waste nutmeg pulp that is not optimally utilized and is thrown into the environment. Nutmeg pulp, which is the largest part of the nutmeg fruit, can be processed into various products. This community service activity aims to provide additional information and knowledge to women's farmer groups (KWT) in Kaiyasa Village to utilize nutmeg pulp waste into a derivative product, namely nutmeg dodol. The methods used in this activity include counseling and training on the utilization of nutmeg waste into a food product, namely nutmeg dodol, accompanied by technology transfer. The activity was carried out in stages, starting with the counseling stage to provide knowledge related to processing nutmeg pulp waste into dodol, followed by product manufacturing training and technology transfer. After the activity, there was an 80% increase in partners' knowledge level regarding the efficiency and utilization of nutmeg pulp waste and product diversification, namely nutmeg dodol, as obtained from the results of pre-tests and post-tests conducted after the counseling and training activities.